Analisis Manajemen Pengajian Gus Iqdam dan Dampaknya terhadap Peningkatan Pendapatan Masyarakat Desa Karanggayam - Oktaviana, Helmalia; Dhani, Rifqi Rama; Mashudi, Mashudi (Journal of Islamic Economic Studies, 2025)
Regular Islamic gatherings function not only as spiritual and social activities but also have the potential to stimulate local economic activity. This study aims to analyze the role of Gus Iqdam’s religious gathering management in improving the income of the Karanggayam Village community. The research employs a qualitative field approach through interviews, observations, and documentation. The findings show that structured management—planning, organizing, implementing, and controlling—can create economic activities that increase vendors’ income. Daily earnings of vendors may rise up to four times compared to regular days. Factors such as business capital, length of business operation, location, and working hours also influence income levels. These findings indicate that the management of religious gatherings can serve as an instrument for community economic empowerment and holds potential to be developed as a model for strengthening community-based economic development.